Implementation of highly sophisticated flow cytometry assays in multicenter clinical studies: considerations and guidance. (May 2015) - Sommer, Ulrike; Morales, Johanna; Groenewegen, Andrea; Müller, Annemarie; Naab, Julia; Woerly, Gaetane; Kamphausen, Esther; Marsot, Helene; Bennett, Patrick; Kakkanaiah, Vellalore; Vitaliti, Alessandra
Flow cytometry is increasingly becoming an important technology for biomarkers used in drug discovery and development. Within clinical development flow cytometry is used for the determination of PD biomarkers, disease or efficacy biomarkers or patient stratification biomarkers. Significant differences exist between flow cytometry methodology and other widely used technologies measuring soluble biomarkers including ligand binding and mass spectrometry. These differences include the very heavy reliance on aspects of sample processing techniques as well as sample stabilization to ensure viable samples. These differences also require exploration of new approaches and wider discussion regarding method validation requirements. This paper provides a review of the current challenges, solutions, regulatory environment and recommendations for the application of flow cytometry to measure biomarkers in clinical development.